Horsing around - Krulik, Nancy E. (Krulik, Nancy E. Katie Kazoo, switcheroo, 2009)
Suzanne is sick of hearing Becky brag about her pony, but she agrees to go with Katie in their class to watch Becky ride at a horse show. During the competition, Katie gets switcherooed into Brownie. Katie has to concentrate if she wants to help Becky win a ribbon, but there's one very big problem-- she can't stop horsing around!